Structure and conceptualization of acceptance: a split-sample exploratory and confirmatory factor analysis approach to investigate the multidimensionality of acceptance of spinal cord injury - Anders Aaby; Sophie Lykkegaard Ravn; Helge Kasch; Tonny Elmose Andersen (Medical Journals Sweden, 2021)
Objective: To determine the multidimensionality of acceptance of spinal cord injury (SCI). Participants: Adults with SCI who were admitted to an SCI centre between 1991 and 2020. Methods: All eligible participants (n=686) were invit-ed to complete a survey via REDCap. A 4-dimensional model was hypothesized, which included "Accepting Reality", "Value Change", "Letting Go of Control" and "Behavioural Engagement". Items from 3 accept-ance scales were selected to collectively reflect these 4 dimensions: (i) Spinal Cord Lesion-related Coping Strategies Questionnaire, (ii) Coping Orientations to Problems Experienced, and (iii) a modified Acceptance and Action Questionnaire. A split-sample principal component analysis (PCA) and confirmatory factor analysis (CFA) approach was used. Results: Complete data were provided by 431 participants (62.8%). A PCA on sub-sample one suggest-ed a 4-factor model based on eigenvalues ≥ 1, corresponding to the hypothesized model of acceptance. A CFA on sub-sample 2 showed good model fit, adding further support to the model. Conclusion: These findings suggest that acceptance is a multidimensional construct with 4 facets that represent distinct, but interconnected, psychological processes. This model of acceptance can be used as a framework for future research and clinical practice to deepen our understanding of acceptance processes following severe injuries, such as SCI. Lay abstract Acceptance has long been considered a core principle of adjustment in rehabilitation psychology. However, several distinct ways of defining and measuring acceptance exist in the literature. The aim of this study was therefore to explore the nuances of acceptance by combining these different definitions in a multidimensional model of acceptance, and testing it empirically. The sample included 431 adults with spinal cord injury who responded to 3 acceptance questionnaires that defined acceptance differently. The statistical analysis showed that acceptance should be regarded a multidimensional construct with 4 facets: "Accepting Reality", "Value Change", "Letting Go of Control" and "Behavioral Engagement". These facets of acceptance reflect distinct, but interconnected, psychological processes, which necessitates a shift in how researchers and healthcare professionals approach this complex topic. We need to be mindful of these nuances in our understanding of acceptance, but also in our measurement strategy and communication with other professionals and patients.